Multiple observers based anti-disturbance control for a quadrotor UAV against payload and wind disturbances - Guo, Kexin; Jia, Jindou; Yu, Xiang; Guo, Lei; Xie, Lihua (Control engineering practice, 2020)
This paper presents a multiple observers based anti-disturbance control (MOBADC) scheme against multiple disturbances for a quadrotor unmanned aerial vehicle (UAV). The quadrotor UAV dynamics can be represented by the Newton’s second law and Lagrange–Euler formalism. The proposed control scheme consists of disturbance observer (DO) based controller and extended state observer (ESO) based controller, which are utilized in the position loop to mainly eliminate the cable suspended payload disturbance with partially known information and mitigate the wind disturbance with bounded variation. What is more, in order to reject the model uncertainty and disturbance moment, another ESO based controller is designed for the attitude loop. Using the proposed control scheme, the anti-disturbance performance can be significantly enhanced. Experimental results in the presence of wind disturbance, payload oscillating disturbance, and hybrid disturbances illustrate the robustness and effectiveness of the proposed method compared to the classical PID method.